Berbagai faktor yang melatarbelakangi kehidupan sehari-hari rumah tangga berdampak terhadap kekuasaan perempuan Bali dalam proses pengambilan keputusan rumah tangga. Tujuan penelitian adalah menguji faktor eksternal dan faktor internal yang mempengaruhi k - Nengah Kartika (Jurnal Ekonomi Kuantitatif Terapan, 2020)
The establishment of LPD Empowerment Institution (LPLPD) in Bali Province has caused a polemic, that polemic was LPD Desa Kedongan did not want to pay the empowerment fund because LPLPD could not open in empowerment fund management. This is a symptom of the main institutional problem - the agent model and overcoming dissatisfaction. This research will be conducted in Bangli Districy and Susut District of Bangli Regency. Therefore, it is necessary to decide the willingness to pay the contribution fee (WTP) to the LPLPD so that it can be determined the tariff that can satisfy all parties. In this study, to determine the tariffs related to public policy, the contingent valuation survey approach is also known as the willingness of the to pay (WTP survey). Looking at this will result in a tariff that will make most LPDs satisfied. This study uses multiple regression analysis to answer the problem formulation. The average WTP is Rp 11,779,000. Based on interviews with respondents, the average respondent willingness to pay the LPLPD empowerment fund to be around 2.95 percent of the profit generated from LPD profit. There are 3 significant variables impact to the willingness to pay LPLPD Empowerment Contributions. These variables include the income, savings and training variables that LPDs are expected to perform by LPLPD.